Islam and Counseling: Model of Practice in Matrilineal System of The Minangkabau Culture - Fadhilla Yusri; Yeni Afrida (Guidena)
Islam and counseling are two things that actually support each other in their practice. Islam states that counseling is a way to help each other between humans. Meanwhile, counseling uses Islam as an approach in counseling services. The Minangkabau community is one of the societies with a very strong Islamic maternal lineage. The purpose of this study was to reveal the appropriate counseling approach for use in the Minangkabau community with all its peculiarities. This research is a library research, where the data required in the research are obtained through analysis of various literatures in the library. Based on the results of the study, it was revealed that in the matrilineal community in Minangkabau, counseling was still new and not very familiar. The material society in Minangkabau has a philosophy of life "adat basandi syara", syara "basandi Kitabullah, where the majority of the people adhere to Islam. The combination of Islam and counseling can pave the way for counseling to gain a place in the hearts of the material community in Minangkabau. It can be concluded that the Islamic approach to counseling is an effective solution for the application of counseling services to the Minangkabau community.